IDENTIFIKASI HAMBATAN BELAJAR SISWA PADA KONSEP PERSAMAAN KUADRAT - Ruli, Redo Martila (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
This research aims to identify learning obstacles and factors that cause learning obstacles experienced by students in learning the concept of quadratic equations. This research used a qualitative approach with the triangulation method, the subjects in this study were 23 class X students who had studied the concept of quadratic equations. The data collection technique in this research was to give a test in the form of a description question consisting of 2 questions to 23 students. Furthermore,  the researchers analyzed each student's answer and then interviewed 3 students who are considered to be able to represent other students in this research to look more deeply into the learning obstacles that students have on the concept of quadratic equations As well as conducting tests and interviews, the researchers made observations when students passed tests. The learning obstacles that the researcher found in the concept of quadratic equation were categorized into ontogenic obstacle, didactic obstacle, and epistemology obstacle. As a final result, the researchers realized: 1) students did not (fully) understand what a quadratic equation meant; 2) students met challenging to represent the problem in algebraic form; 3) students were able to overcome quadratic equations (test) in single way.